Dynamics of non-equilibrium 6Li Feshbach molecules via magnetic field ramp - Naniyil, Vineetha (2022)
In this thesis, the dynamics of Feshbach molecule formation via magnetic field ramp is investigated. The work presented in this thesis dealt with production and study of bosonic Feshbach molecule from fermionic 6Li atoms by quenching the magnetic field across the broad Feshbach resonance at 834.1 G. The fraction of atoms converted to Feshbach molecules is measured experimentally and the dependence of temperature and the rate at which the magnetic field is ramped during the process has been presented. The formation of Feshbach molecule via magnetoassociation of ultracold 6Li atoms close to quantum degeneracy is also explored in this thesis.